Process evaluation of a National Primary Eye Care Programme in Rwanda - Jennifer L. Y. Yip; Tess Bright; Sebastian Ford; Wanjiku Mathenge; Hannah Faal; on behalf of the Rwanda Primary Eye Care Process evaluation group (BMC, 2018)
Abstract Background Visual impairment is a global public health problem, with an estimated 285 million affected globally, of which 43% are due to refractive error. A lack of specialist eye care in low and middle-income countries indicates a new model of care would support a task-shifting model and address this urgent need. We describe the features and results of the process evaluation of a national primary eye care (PEC) programme in Rwanda. Methods We used the Medical Research Council process evaluation framework to examine the implementation of the PEC programme, and to determine enablers and challenges to implementation. The process evaluation uses a mixed methods approach, drawing on results from several sources including a survey of 574 attendees at 50 PEC clinics, structured clinical observations of 30 PEC nurses, in-depth interviews with 19 key stakeholders, documentary review and a participatory process evaluation workshop with key stakeholders to review collated evidence and contextualize the results. Results Structured clinical assessment indicated that the PEC provided is consistent with the PEC curriculum, with over 90% of the clinical examination processes conducted correctly. In 4 years, programme monitoring data showed that nearly a million PEC eye examinations had been conducted in every health centre in Rwanda, with 2707 nurses trained. The development of the eye health system was an important enabler in the implementation of PEC, where political support allowed key developments such as inclusion of eye-drops on the essential medicines list, the inclusion of PEC on insurance benefits, the integration of PEC indicators on the health management information systems and integration of the PEC curriculum into the general nursing school curriculum. Challenges included high turnover of primary care nurses, lack of clarity and communication on the future funding of the programme, competing priorities for the health sector and sustained supervision to assure quality of care. Conclusions A model of a national primary eye care programme is presented, with service delivery to all areas in Rwanda. Key learning from this evaluation is the importance of strengthening the eye health care system, together with a strong focus on training primary care nurses using a PEC curriculum.